2022
DOI: 10.3389/fonc.2022.1026020
|View full text |Cite
|
Sign up to set email alerts
|

Unweaving the mitotic spindle: A focus on Aurora kinase inhibitors in lung cancer

Abstract: Lung cancer is one of the most aggressive malignancies, classified into two major histological subtypes: non-small cell lung cancer (NSCLC), that accounts for about 85% of new diagnosis, and small cell lung cancer (SCLC), the other 15%. In the case of NSCLC, comprehensive genome sequencing has allowed the identification of an increasing number of actionable targets, which have become the cornerstone of treatment in the advanced setting. On the other hand, the concept of oncogene-addiction is lacking in SCLC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Additionally, c-Myc expression and mutations were identified as potential predictive biomarkers of alisertib. The disease control rate, defined as the combination of complete response, partial response, and stable disease lasting at least 8 weeks, was significantly higher with alisertib/paclitaxel compared to placebo/paclitaxel (55% versus 33%) in the subgroup of resistant or refractory patients efficacy [118]. Among c-Myc-positive patients, the median progression-free survival was 4.64 months with alisertib/paclitaxel, whereas it was 2.27 months with placebo/paclitaxel.…”
Section: New Drugs In the Second Line Or Beyondmentioning
confidence: 93%
“…Additionally, c-Myc expression and mutations were identified as potential predictive biomarkers of alisertib. The disease control rate, defined as the combination of complete response, partial response, and stable disease lasting at least 8 weeks, was significantly higher with alisertib/paclitaxel compared to placebo/paclitaxel (55% versus 33%) in the subgroup of resistant or refractory patients efficacy [118]. Among c-Myc-positive patients, the median progression-free survival was 4.64 months with alisertib/paclitaxel, whereas it was 2.27 months with placebo/paclitaxel.…”
Section: New Drugs In the Second Line Or Beyondmentioning
confidence: 93%
“…Overexpression of Aurora kinases (AURKs) is a prevalent protumorigenic pathway in numerous cancer types, including SCLC [ 41 ]. In particular, in p53-deficient cells, the protumorigenic effects of the AURKs are even augmented [ 42 ].…”
Section: Targeted Therapies In P53 and Rb Deficient Sclc Cellsmentioning
confidence: 99%
“…The promising activity of alisertib/paclitaxel in relapsed or refractory SCLC was confirmed by the 3.2 months median progression-free survival (mPFS) for alisertib/paclitaxel compared to 2.17 months for placebo/paclitaxel (hazard ratio (HR) = 0.77) [ 45 ]. Preliminary clinical trials revealed significant indications of AURK inhibitors’ effectiveness, especially when combined with taxanes [ 41 ], but these findings require validation through phase III randomized trials.…”
Section: Targeted Therapies In P53 and Rb Deficient Sclc Cellsmentioning
confidence: 99%
“…Additionally, Alisertib (MLN8237), a selective inhibitor of AURKA, has demonstrated improvement in PFS when combined with paclitaxel compared to paclitaxel alone in patients with SCLC tumors positive for C-MYC [ 87 ]. As a caveat, Aurora K inhibitor effectiveness and safety must be carefully validated in phase 3 clinical trials, as many patients, despite showing an initial good response, have had to discontinue treatment due to tumor progression or adverse effects, particularly those linked to blood malignancies [ 88 ].…”
Section: Actionable Drivers In Sclcmentioning
confidence: 99%